(untitled) (Economic studies journal, 2022)
This study aimed to identify the most important determinants of Libya’s foreign trade with Italy as one of its most important trading partners through the Gravity Model using a standard logarithmic equation according to the ARDL methodology that included many explanatory variables including (GDP in Libya and Italy, population in Libya, GDP per capita in Italy, the geographic distance variable between Libya and Italy, in addition to a dummy variable representing the impact of economic sanctions during the Lockerbie crisis on the trade flow between them), while the dependent variable was expressing the total foreign trade in both parts (exports and imports) for Libya during The time period (1990 - 2020), and after making estimates for the regression of the independent variables, the results showed that there is statistical and economic significance for all the independent variables on the dependent variable, and that the dependent variable in the time period (1-) has a significant effect on itself in the current period at a level of significance 5%, and all variables Signals was according to the assumptions of the economic theory, except for the variable ( Population in Libya) . The results also indicated the existence of a Long Run relationship between (GDP per capita in Italy, GDP of Italy, GDP of Libya, economic distance between Libya and Italy) with the trade flow between Libya and Italy.